2020
DOI: 10.1111/ecin.12924
|View full text |Cite
|
Sign up to set email alerts
|

The Performance Effects of Wise and Unwise Managerial Dismissals

Abstract: The decision to dismiss a coach is challenging because poor performance tends to coincide with both bad luck and low coaching ability. We differentiate between dismissals following actual poor performance on the pitch (wise dismissals) and dismissals following seemingly poor performance due to bad luck (unwise dismissals). To categorize dismissals, we use "expected goals," which are less vulnerable to random variation in match outcomes. Using data from European football, we find that wise dismissals increase s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 27 publications
(48 reference statements)
0
18
0
Order By: Relevance
“…Many laboratory studies have found an outcome bias in different settings, e.g., legal decisions (Alicke, Davis & Pezzo, 1994), medical decisions (Baron & Hershey, 1988), investment decisions (König-Kersting, Pollmann, Potters, & Trautmann, 2021;Ratner & Herbst, 2005) and ethical judgments (Gino, Moore & Bazerman, 2009;Gino, Shu & Bazerman, 2010). Consistent with the literature of psychology and economics, recent research in sports economics has also shown that decision-makers underestimate the role of randomness in match outcomes and assign too much weight to the observed outcomes when they evaluate performance (Flepp & Franck, 2021;Gauriot & Page, 2019;Kausel, Ventura & Rodríguez, 2019;Lefgren, Platt & Price, 2015).…”
Section: Introductionmentioning
confidence: 77%
See 4 more Smart Citations
“…Many laboratory studies have found an outcome bias in different settings, e.g., legal decisions (Alicke, Davis & Pezzo, 1994), medical decisions (Baron & Hershey, 1988), investment decisions (König-Kersting, Pollmann, Potters, & Trautmann, 2021;Ratner & Herbst, 2005) and ethical judgments (Gino, Moore & Bazerman, 2009;Gino, Shu & Bazerman, 2010). Consistent with the literature of psychology and economics, recent research in sports economics has also shown that decision-makers underestimate the role of randomness in match outcomes and assign too much weight to the observed outcomes when they evaluate performance (Flepp & Franck, 2021;Gauriot & Page, 2019;Kausel, Ventura & Rodríguez, 2019;Lefgren, Platt & Price, 2015).…”
Section: Introductionmentioning
confidence: 77%
“…Consistent with insights from the laboratory, a few studies have provided the first evidence of the outcome bias in the field (Emerson et al, 2010;Tinsley, Dillon & Cronin, 2012). Recently, research in sports economics has shown that decision-makers underestimate the role of randomness in match outcomes and assign too much weight to the observed outcomes when they evaluate performance (Flepp & Franck, 2021;Gauriot & Page, 2019;Kausel et al, 2019;Lefgren et al, 2015). Using a formal model based on Bayesian updating, Lefgren et al (2015) found that coaches in the NBA change their strategy more often after losing a game than after winning a game, even when comparing narrow wins and losses.…”
Section: Outcome Biasmentioning
confidence: 93%
See 3 more Smart Citations